(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Ocimum sanctum Linn extract as an adjuvant therapy for effective glycaemic control in type II diabetes mellitus, a case control study was conducted at selected hospitals of Sangli, Miraj, Kupwad corporation area. The objectives of the study were to assess the blood glucose levels in diabetic patients before and after treatment with Ocimum sanctum Linn extract combined with oral hypoglycaemic agent and to compare these blood glucose levels in experimental and control groups. The hypothesis H0 was that there would be no significant difference between after the administration of Ocimum sanctum Linn leaves extract on blood sugar level of experimental and control group and H1 there is significant difference between pre-test and post-test blood sugar level of experimental and control group. The study used the quantitative research approach. The conceptual framework was used in this study was ERNESTINE WIEDENBACHS PRESCRIPTIVE THEORY. Total 60 samples were selected for the study by non-probability convenient sampling technique (30 for experimental 30 for control group). Experimental group had given Ocimum sanctum Linn extract with OHA for 20 days,whereas control group continued OHA treatment only. Demographic variables and blood glucose level data was collected. The data was analysed using the descriptive and inferential statistics such as mean, standard deviation, frequency and percentage were utilised as well as inferential analysis such as chi square test, paired t and unpaired t test. The study results suggested that the mean value of pre and post-test fasting blood glucose levels in the experimental group were 166.00 and 132.37 mg% respectively. The mean pre-test and post-test fasting blood glucose levels in control group were 169.63 and 163.50 mg% respectively. The mean value of pre and post-test post prandial blood glucose levels in the experimental group were 170.27 and 141.31 mg% respectively. The mean pre-test and post-test post prandial blood glucose levels in control group were 166.47 and 159.87 mg% respectively. The result of comparison of post prandial blood glucose levels in experimental and control groups had calculatedt value of 50.18 and pvalueof0.000 which suggests that there is a significant difference in the post prandialblood sugar levels of the experimental and the control groups. The study concluded that Ocimum sanctum Linn can be recommended for the treatment of moderate diabetes mellitus in combination with oral hypoglycaemic agents to get the synergistic effect of both the medicines for effective control of hyperglycemia.